Unexpected challenges faced by caregivers of children with neurogenic bladder: A qualitative study. Issue 4 (August 2022) - Flewelling, Kassie D.; Wengryn, Derek M.; Buchanan, Cindy L.; Beltran, Gemma P.; Vemulakonda, Vijaya M.; Hecht, Sarah L.
Summary: Background: Management of the neurogenic bladder is variable, complex, and often requires a demanding bladder care regimen which may present caregiver burdens that are unique among chronic disease. While research into patient quality of life is increasing, parallel study of the caregiver experience is scant. Existing research primarily comprises survey data using validated instruments originally developed for non-urologic conditions, such as dementia. These surveys may detect high caregiver burden and decreased quality of life amongst caregivers but are limited in their ability to understand the underlying causes. Objective: To characterize the experience of those caring for children with neurogenic bladders, with a focus on unexpected burdens and challenges. Methods: In light of limited existing research, a qualitative research methodology was selected to explore the caregiver experience. Semi-structured phone interviews were conducted with primary caregivers of children with neurogenic bladder, all of whom were patients in the pediatric urology department of a single tertiary pediatric referral center. Purposive sampling was used to ensure diverse representation. Interviews were recorded, transcribed, and professionally translated if needed. Transcripts were analyzed using a team-based inductive grounded-theory approach, facilitated by ATLAS. ti software. Member-checking focus groups were held to validate the results. Results: Twenty-five caregivers were interviewed (20 in English, 5 in Spanish), at which point thematic saturation was reached. Three primary themes emerged surrounding the topic of unexpected challenges: 1. High caregiver burden, 2. Challenges with catheterization and supplies, 3. Urinary tract infections. Member-checking focus groups validated the thematic analysis and provided additional insights into mitigating factors for these challenges. A child's independence with his or her health care regimen was cited as particularly important for decreasing caregiver burden. Discussion: Caregivers of children with neurogenic bladder report their role is more difficult than they anticipated it would be. Catheterization represents a particularly burdensome task, and recurrent infections are an unexpected and persistent medical challenge. Understanding unexpected challenges that caregivers face will help pediatric urologists target modifiable factors to decrease caregiver burden, address current gaps in counseling and expectation-setting, and set the stage for more complete shared decision-making. Conclusions: This study represents an initial qualitative characterization of the experience caring for a child with neurogenic bladder. This is a key first step in understanding how caregivers make decisions for their children and their families. This initial study is foundational to a larger project to create a decision aid for caregivers of children with neurogenic bladder.